Characterization and Reliability of [18F]2FNQ1P in Cynomolgus Monkeys as a PET Radiotracer for Serotonin 5-HT6 Receptors - Véronique Sgambato-Faure; Véronique Sgambato-Faure; Thierry Billard; Thierry Billard; Elise Météreau; Elise Météreau; Sandra Duperrier; Sandra Duperrier; Sylvain Fieux; Sylvain Fieux; Nicolas Costes; Léon Tremblay; et al. (Frontiers Media S.A., 2017)
Brain serotonin-6 receptor (5-HT6R) is the one of the most recently identified serotonin receptors. Accumulating evidence suggests that it is a potent therapeutic target for psychiatric and neurological diseases. Since [18F]2FNQ1P was recently proposed as the first fluorinated positron emission tomography (PET) radioligand for this receptor, the objective of the present study was to demonstrate its suitability for 5-HT6R neuroimaging in primates. [18F]2FNQ1P was characterized by in vitro autoradiography and in vivo PET imaging in cynomolgus monkeys. Following in vivo PET imaging, tracer binding indices were computed using the simplified reference tissue model and Logan graphical model, with cerebellum as reference region. The tracer binding reproducibility was assessed by test-retest in five animals. Finally, specificity was assessed by pre-injection of a 5-HT6R antagonist, SB258585. In vitro, results showed wide cerebral distribution of the tracer with specificity toward 5-HT6Rs as binding was effectively displaced by SB258585. In vivo brain penetration was good with reproducible distribution at cortical and subcortical levels. The automated method gave the best spatial normalization. The Logan graphical model showed the best tracer binding indices, giving the highest magnitude, lowest standard deviation and best reproducibility and robustness. Finally, 5-HT6R antagonist pre-injection significantly decreased [18F]2FNQ1P binding mainly in the striatum and sensorimotor cortex. Taken together, these preclinical results show that [18F]2FNQ1P is a good candidate to address 5-HT6 receptors in clinical studies.